2018
DOI: 10.1590/1678-4324-2018180303
|View full text |Cite
|
Sign up to set email alerts
|

Brown Flaxseed Prevents DNA Damage Induced by 1,2-Dimethylhydrazine in a Pre-Clinical Model

Abstract: The study evaluated the effects of brown flaxseed supplementation in natura on the prevention of DNA damage induced by 1,2-dimethylhydrazine (DMH) in vivo. The experimental groups were Negative and Positive Controls and the protocols of Pre-treatment, Simultaneous, Post-treatment, Pre+continuous in relation to the supplementation of brown flaxseed and administration with carcinogenic compound. The results showed that brown flaxseed supplementation does not cause genomic and genetic damage. In addition, brown f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Another fact that can explain this finding is that the spleen of rats is very proficient in sequestering cells with DNA damage (genomic damage—comet; chromosomal damage—micronuclei) [ 62 ] compared to mice, for example. These data are corroborated by studies carried out with mice that demonstrated that DMH was capable of causing genotoxic damage [ 10 , 11 , 14 , 19 , 24 ]. The study by Pesarini et al [ 10 ] demonstrated that DMH (30 mg/Kg) caused an average frequency of 99.60 ± 0.22 injured cells for every 100 cells analyzed.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Another fact that can explain this finding is that the spleen of rats is very proficient in sequestering cells with DNA damage (genomic damage—comet; chromosomal damage—micronuclei) [ 62 ] compared to mice, for example. These data are corroborated by studies carried out with mice that demonstrated that DMH was capable of causing genotoxic damage [ 10 , 11 , 14 , 19 , 24 ]. The study by Pesarini et al [ 10 ] demonstrated that DMH (30 mg/Kg) caused an average frequency of 99.60 ± 0.22 injured cells for every 100 cells analyzed.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, NFRFP increased chow total dietary fiber by 20.94%, a desired characteristic since dietary fibers may be associated with decreased incidence of colorectal cancer. Diet fiber exerts beneficial effects such as increasing fecal volume, regulating intestinal flora, and promoting the dilution and/or adsorption of possible carcinogens [ 6 , 8 , 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations